Bacterial Gamma-Glutamyl Transpeptidase, an Emerging Biocatalyst: Insights Into Structure–Function Relationship and Its Biotechnological Applications - Saini, Meenu; Kashyap, Amuliya; Bindal, Shruti; Saini, Kuldeep; Gupta, Rani (Frontiers in Microbiology, 2021)
Gamma-glutamyl transpeptidase (GGT) enzyme is ubiquitously present in all life forms and plays a variety of roles in diverse organisms. Higher eukaryotes mainly utilize GGT for glutathione degradation, and mammalian GGTs have implications in many physiological disorders also. GGTs from unicellular prokaryotes serve different physiological functions in Gram-positive and Gram-negative bacteria. In the present review, physiological significance of bacterial GGTs has been discussed categorising GGTs from Gram-negative bacteria like E. coli as glutathione degraders and from pathogenic species like H. pylori as virulence factors. Gram-positive bacilli, however, are considered separately as poly-γ-glutamic acid (PGA) degraders. Structure-function relationship of the GGT is also discussed mainly focusing on crystallization of bacterial GGTs along with functional characterization of conserved regions by site directed mutagenesis that unravels molecular aspects of autoprocessing and catalysis. Only a few crystal structures have been deciphered so far. Further, different reports on heterologous expression of bacterial GGTs in E. coli and Bacillus subtilis as hosts have been presented in a table pointing towards lack of fermentation studies for a large-scale production. Physico-chemical properties of bacterial GGTs have also been described, followed by detailed discussion on the various applications of the bacterial GGTs in different biotechnological sectors. This review emphasizes the potential of bacterial GGTs as an industrial biocatalyst relevant to the current switch towards green chemistry.